BRAZIL AND RIO+10 - Ribeiro, Wagner Costa (Revista do Departamento de Geografia, 2011)
Major international events gathering people from different countries enlarge and help to institutionalize environmental issues. The World’s Conference on Sustainable Development kept on the movement that intends to regulate international human actions on the environment and to reinforce the international environmental order. The author also analyzes the Implementation Plan approved in Johannesburg as well as the possibility of its application in Brazil, and discusses the Brazilian proposals to the Conference.